(untitled) (Archaeologia Adriatica, 2020)
Overview of scientific and professional work of the archaeologist Šime Batović, PhD, full professor has been presented to the archaeological and wide public on more than one occasion. Even so, it is still not thoroughly evaluated. This foreword is only a very brief summary of his scholarly qualities, with selected biographic or bibliographic information. It should present importance of his complex work, what determined and shaped it, making it fundamental and permanent in Croatian prehistoric archaeology.